PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 RAO SELATAN - Sisi Yulanda (Jurnal Edukasi dan Penelitian Matematika, 2022)
Mathematical communication skills is one of that is expected to developed in learning mathematics, but that happens on the field have not been able to optimize the capabilities. This is because of the learning strategies that are not appropriate with the student’s learning style. This situation impacts on students mathematics learning class VIII in Junior High School 1 Rao Selatan outcomes are mostly still lower than the Minimum Completeness Criteria. One of attempt to do is Problem Based Learning (PBL) model for improving students mathematical communication skills at class VIII Junior High School 1 Rao Selatan. This research showed that  students mathematical communication skills which using PBL model better than using conventional learning Keywords— Mathematical communication, Problem Based Learning, Conventional learning.